Isolation and Identification of Subgroup J Avian Leukosis Virus Inducing Multiple Systemic Tumors in Parental Meat-Type Chickens - Cui, Ning; Cui, Xuezhi; Huang, Qinghua; Yang, Shaohua; Su, Shuai; Xu, Chuantian; Li, Jianhe; Li, Wenfeng; Li, Chao (Frontiers in Veterinary Science, 2021)
Avian leukosis virus (ALV) continues evolving to obtain new genomic characters to enhance its pathogenicity. In the present study, an ALV-J strain LH20180301 was isolated from broiler breeder chickens that reached the speak of paralyzation before 20-week-old. The necropsy chickens showed subcutaneous and muscular hemorrhage, and developed tumors in multiple organs including bone, liver, spleen, and kidney. The complete provirus was then cloned and sequenced to investigate the molecular characteristics and oncogenicity etiology of this virus associated with the outbreak of disease. The genomic structure of the reported ALV-J strain LH20180301 was highly conservative with other ALVs. Recombination events between the virus with endogenous virus were identified in the viral genome. Compared with the ALV-J original HPRS-103 strain, the major recombination sites of the viral genome with ev-1 were located in 5’UTR-gag and 3’UTR regions. Phylogenetic analysis of group specific antigen gp85 encoding protein showed that the LH20180301 branched with ALV-J prevalent in “yellow chickens” of local breeds in South China. Nine amino acids (N58, D60, K70, A71, K108, N112, N113, N121, R272) in the gp85 were highly conserved among ALV-J isolates before 2012, but various mutations were found in the late isolates including LH20180301. In addition, the LH20180301 strain also had the same deletion pattern of 3’UTR with them. Therefore, LH20180301 might derive from the same ancestor with those viruses and may be the trend of ALV-J evolution in China. The defined new genomic characters in the gp85 and 3’UTR region of ALV-J might provide the molecular basis for its enhanced oncogenicity.